Composite material for plastic products and production method thereof

By surface grafting modification of maifanite fibers and composited with polyethylene, the problem of poor compatibility between fibers and polyethylene substrates is solved, and the mechanical strength of polyethylene composite materials is significantly improved, meeting the high-strength needs.

CN119529406AInactive Publication Date: 2025-02-28JIANGXI LINGYUE MATERIAL TECH CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411787816.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-06
Publication Date
2025-02-28
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing polyethylene composite materials cannot meet the high requirements of some industries in terms of mechanical strength, especially due to the poor compatibility between fibers and polyvinyl matrix, resulting in poor fiber reinforcement effect.

Method used

By surface modification of maifanite fibers, graft modification is performed using silane coupling agent and macromolecular graft-modified polymers to form maifanite fiber reinforcement with epoxy groups on the surface, combining high-density polyethylene and compatibility agents and preparing composite materials using mechanical stirring and twin-screw extrusion mechanism.

Benefits of technology

It has achieved good compatibility and a firm snap-on structure between maifanite fiber and polyvinyl matrix, significantly improved the mechanical strength of the composite material and met the high requirements for material strength in some industries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119529406A_ABST
    Figure CN119529406A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of materials, and discloses a composite material for plastic products and a production method thereof.The composite material is prepared by taking high-density polyethylene as a base material and mixing and granulating the base material with auxiliary materials such as a compatilizer, a medical stone fiber reinforcing agent and an ultraviolet absorbent. The medical stone fiber reinforcing agent can interact with a maleic anhydride group in a compatilizer structure, and a mutually entangled interwoven network structure can be generated between a branched molecular chain on the surface and a polyethylene molecular chain, so that the medical stone fiber can exist in the composite material in a cross-linked core form; according to the medical stone fiber reinforced polyethylene composite material, the problem of poor compatibility between the medical stone fiber and the polyethylene matrix can be solved, and a firm buckle type structure can be generated between the medical stone fiber and the polyethylene matrix, so that the medical stone fiber can efficiently exert a self-reinforcing effect, and the mechanical strength of polyethylene is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of materials, and in particular to a composite material for plastic products and a production method thereof. Background Art

[0002] Polyethylene (PE for short) is a widely used plastic material with the advantages of low cost, good processing performance, wide application fields and environmental protection. Due to its unique physical and chemical properties, it has been widely used in packaging materials, pipes, cables, fibers, automobiles, electronic equipment and other fields. Its excellent performance and cost-effectiveness make it one of the indispensable materials in these fields, so it occupies an important position in the plastics industry.

[0003] However, with the continuous advancement of science and technology, the requirements for various performance of materials are gradually increasing, especially the requirements for the mechanical strength of materials are higher. Although the mechanical strength of polyethylene is acceptable, it has gradually failed to meet the use needs of some industries. Therefore, the preparation of polyethylene composite materials with better mechanical strength is of great significance for the further application of polyethylene.

[0004] The invention patent with publication number CN115260636B discloses a fiber-reinforced polyethylene plastic and a preparation method thereof. By using glass fiber to reinforce and modify polyethylene, the mechanical strength of polyethylene can be effectively enhanced. However, there are obvious interface problems between inorganic materials and polymer materials. In fact, it is difficult to effectively exert the reinforcing effect of the fiber. Therefore, it is necessary to perform surface modification on inorganic materials such as fibers.

[0005] Based on this, the present invention provides a polyethylene composite material, which has excellent mechanical strength and can be directly used to make plastic products. Summary of the invention

[0006] In order to solve the problems mentioned in the background technology, the object of the present invention is to provide a composite material for plastic products and a production method thereof.

[0007] The purpose of the present invention can be achieved through the following technical solutions: A method for producing a composite material for plastic products, the composite material comprising the following raw materials in parts by weight: High density polyethylene 68-72 parts; Compatibilizer 5-15 parts; Medical stone fiber reinforcing agent 2-3.5 parts; 0.5-1.5 parts of UV absorber; Antioxidant 0.5-1.2 parts; 2-5 parts of inorganic powder additives; 1-2 parts of lubricant; The production method specifically comprises the following steps: Step S1, weigh and prepare the raw materials in order according to their weight and set aside; Step S2, putting the prepared raw materials into a stirring kettle, controlling the temperature to 100-120°C, the rotation speed to 2000-3000r / min, mechanically stirring and mixing for 30-60min, cooling and discharging the materials to form a precursor material; Step S3, feeding the precursor material into a twin-screw extruder, controlling the temperature of each zone of the extruder in sequence: zone 1 220±5°C, zone 2 230±5°C, zone 3 240±5°C, zone 4 240±5°C, zone 5 230±5°C, the screw speed is 50-60rpm, and the composite material can be obtained by melt extrusion and granulation.

[0008] As a further embodiment of the present invention, the compatibilizer is maleic anhydride grafted polypropylene or maleic anhydride grafted polyethylene.

[0009] As a further embodiment of the present invention, the preparation method of the medical stone fiber reinforcing agent comprises the following steps: Step SS1, dispersing medical stone fiber in 70% ethanol aqueous solution by volume, ultrasonicating for 20-40 minutes, adding epoxy silane coupling agent to the dispersion, and after adding, controlling the temperature to 70-80°C, stirring for 3-6 hours, separating the material, and obtaining the fiber intermediate material; Step SS2, adding the fiber intermediate material to toluene, ultrasonically treating for 30-60 minutes to form a uniform dispersion, then adding the macromolecular grafted modified polymer and the phase transfer catalyst, after adding, gradually raising the temperature to 60-70°C, keeping warm for 6-9 hours, separating the material, and obtaining the medical stone fiber reinforcing agent; As a further scheme of the present invention, in step SS1, the epoxy silane coupling agent is 3-glycidyloxypropyltrimethoxysilane or 3-glycidyloxypropyltriethoxysilane; the mass ratio of the medical stone fiber and 3-glycidyloxypropyltriethoxysilane is 2.6g:3.5g; in step SS2, the mass ratio of the toluene, the fiber intermediate material, the macromolecular grafted modified polymer, and the phase transfer catalyst is 20g:2.4g:6.5g:0.1g.

[0010] As a further embodiment of the present invention, in step SS2, the phase transfer catalyst is any one of tetrabutylammonium hydrogen sulfate, tetrabutylammonium bromide, tetramethylammonium bromide or tetrabutylammonium chloride.

[0011] In the above technical scheme, the surface of medical stone fiber is first modified by using a silane coupling agent to obtain a medical stone fiber intermediate material whose surface is modified with epoxy groups. Then, under the catalytic action of a phase transfer catalyst, the epoxy substituents of the fiber intermediate material can undergo ring-opening esterification with the active carboxyl substituents in the macromolecular grafted modified polymer structure to obtain medical stone fiber with a macromolecular polymer grafted on the surface, namely, a medical stone fiber reinforcer.

[0012] As a further embodiment of the present invention, in step SS2, the preparation method of the macromolecular graft-modified polymer is as follows: Add diphenolic acid and toluene solvent to a polymerization kettle filled with nitrogen, start stirring after adding, and after forming a uniform solution, add sodium hydroxide aqueous solution to the polymerization kettle, start heating after adding, raise the temperature to 50-60° C., keep warm for 1-2 hours, then add a branching linker to the polymerization kettle, further raise the temperature to 70-80° C., keep warm and stir for 8-16 hours, evaporate and remove the solvent, separate the product, and obtain a macromolecular graft-modified polymer; The usage ratio of diphenolic acid, toluene solvent, sodium hydroxide aqueous solution and branching linker is 0.4 g: 2 mL: 1 mL: 0.54 g.

[0013] As a further embodiment of the present invention, the mass fraction of the sodium hydroxide aqueous solution is 20-30%.

[0014] As a further embodiment of the present invention, the branching linker is tetrabromoneopentane.

[0015] In the above technical scheme, sodium hydroxide is first used to activate diphenolic acid, and then a branching linker is used to continuously replace it under high temperature conditions to form a polyether branched polymer with a dendritic structure, that is, a macromolecular grafted modified polymer.

[0016] As a further embodiment of the present invention, the ultraviolet absorber is ultraviolet absorber UV-234 or ultraviolet absorber UV-120; the antioxidant is antioxidant 1076 or antioxidant 168; the inorganic powder additive is any one of talcum powder, titanium dioxide or fumed silica; and the lubricant is paraffin or polyethylene wax.

[0017] A composite material for plastic products is prepared by adopting the production method.

[0018] Beneficial effects of the present invention: The medical stone fiber reinforcing agent prepared by the present invention is medical stone fiber with a hyperbranched macromolecular polymer modified on the surface. In the subsequent high-temperature mixing process, since the hydroxyl group generated by the ring-opening esterification can interact with the maleic anhydride group in the compatibilizer structure, the branched molecular chains can generate an intertwined interwoven network structure with the polyethylene molecular chains, so that the medical stone fiber can exist in the material in the form of a cross-linked core, which can not only solve the problem of poor compatibility between the medical stone fiber and the polyethylene matrix, but also generate a firm snap-on structure between the medical stone fiber and the polyethylene matrix, thereby enabling the medical stone fiber to efficiently exert its own reinforcing effect and improve the mechanical strength of polyethylene.

[0019] Of course, any product implementing the present invention does not necessarily need to achieve all of the advantages described above at the same time. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings required for describing the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying creative work.

[0021] Figure 1 This is the infrared analysis test diagram of the macromolecular grafted modified polymer. DETAILED DESCRIPTION

[0022] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0023] Preparation Example 1 Preparation of medical stone fiber reinforcing agent: Step SS1, dispersing 2.6g medical stone fiber in 15g ethanol aqueous solution with a volume fraction of 70%, ultrasonically treating for 30min, adding 3.5g 3-glycidyloxypropyltriethoxysilane to the dispersion, after adding, controlling the temperature to 75°C, stirring for 4h, separating the material, and obtaining the fiber intermediate material; The epoxy value of the fiber intermediate material was tested by hydrochloric acid-acetone titration test method. 0.1g was taken as the test sample. The specific test method referred to the standard GB / T 1677-2008. The test results showed that the epoxy value of the sample was 4.181mmol / g. Step SS2, add 2.4g of fiber intermediate material to 20g of toluene, ultrasonically treat for 40min to form a uniform dispersion, then add 6.5g of macromolecular grafted modified polymer and 0.1g of tetrabutylammonium bromide. After the addition, gradually increase the temperature to 65°C, keep warm for 8h, separate the material, and you can get the medical stone fiber reinforcer.

[0024] 0.1g of medical stone fiber reinforcement was taken as the test sample and the epoxy value test was performed again. The test results showed that the epoxy value of the sample was 0.584mmol / g, which was caused by the consumption of epoxy groups during the grafting reaction.

[0025] The preparation method of the macromolecular grafted modified polymer is as follows: Add 0.4 g of diphenolic acid and toluene solvent to a polymerization kettle filled with nitrogen. After the addition, start stirring. After a uniform solution is formed, add 1 mL of a 30% by mass sodium hydroxide aqueous solution to the polymerization kettle. After the addition is completed, start heating and raise the temperature to 60°C. After keeping warm for 2 hours, add 0.54 g of tetrabromoneopentane to the polymerization kettle, further increase the temperature to 75°C, keep warm and stir for 12 hours, evaporate and remove the solvent, separate the product, and obtain a macromolecular grafted modified polymer with a purity of 99.5%.

[0026] The macromolecular grafted modified polymer was made into potassium bromide tablets and subjected to infrared analysis test. The results are shown in Figure 1 , of which 3401cm -1 The absorption peak at 3000-3100cm is the characteristic absorption peak of hydroxyl. -1 The absorption peak at 1732 cm is the characteristic absorption peak of carbon and hydrogen on the benzene ring. -1 The absorption peak at 1099cm is the characteristic absorption peak of the carbon-oxygen double bond of the carboxyl group. -1 The absorption peak appearing at is the characteristic absorption peak of the ether bond produced by the substitution reaction. Example 1

[0027] A composite material for plastic products, comprising the following raw materials in parts by weight: High density polyethylene 68 parts; 5 parts of compatibilizer; 2 parts of medical stone fiber enhancer; Ultraviolet absorber UV-120 0.5 parts; Antioxidant 1076 0.5 parts; 2 parts of talcum powder; 1 part paraffin; The production method of the composite material specifically comprises the following steps: Step S1, weigh and prepare the raw materials in order according to their weight and set aside; Step S2, putting the prepared raw materials into a stirring kettle, controlling the temperature to 100° C. and the rotation speed to 2000 r / min, mechanically stirring and mixing for 60 minutes, cooling and discharging the materials to form a precursor material; Step S3, feeding the precursor material into a twin-screw extruder, controlling the temperature of each zone of the extruder in sequence: zone 1 220°C, zone 2 230°C, zone 3 240°C, zone 4 240°C, zone 5 230°C, the screw speed is 50rpm, and the composite material can be obtained by melt extrusion and granulation.

[0028] The preparation method of medical stone fiber reinforcing agent is shown in Preparation Example 1; the compatibilizer adopts maleic anhydride grafted polyethylene with a grafting rate of 1%, and the same applies to the following. Example 2

[0029] A composite material for plastic products, comprising the following raw materials in parts by weight: High density polyethylene 70 parts; Compatibilizer 12 parts; 3 parts of medical stone fiber enhancer; 1 part of UV absorber UV-234; Antioxidant 168 1 part; 3 parts of talcum powder; 1.5 parts of paraffin; The production method of the composite material specifically comprises the following steps: Step S1, weigh and prepare the raw materials in order according to their weight and set aside; Step S2, putting the prepared raw materials into a stirring kettle, controlling the temperature to 110° C. and the rotation speed to 2500 r / min, mechanically stirring and mixing for 40 minutes, cooling and discharging the materials to form a precursor material; Step S3, feeding the precursor material into a twin-screw extruder, controlling the temperature of each zone of the extruder in sequence: zone 1 220°C, zone 2 230°C, zone 3 240°C, zone 4 240°C, zone 5 230°C, the screw speed is 50rpm, and the composite material can be obtained by melt extrusion and granulation. Example 3

[0030] A composite material for plastic products, comprising the following raw materials in parts by weight: High density polyethylene 72 parts; 15 parts of compatibilizer; 3.5 parts of medical stone fiber reinforcing agent; 1.5 parts of ultraviolet absorber UV-234; Antioxidant 168 1.2 parts; 5 parts of talcum powder; 2 parts paraffin; The production method of the composite material specifically comprises the following steps: Step S1, weigh and prepare the raw materials in order according to their weight and set aside; Step S2, putting the prepared raw materials into a stirring kettle, controlling the temperature to 120°C and the rotation speed to 3000r / min, mechanically stirring and mixing for 30 minutes, cooling and discharging the materials to form a precursor material; Step S3, feeding the precursor material into a twin-screw extruder, controlling the temperature of each zone of the extruder in sequence: zone 1 220°C, zone 2 230°C, zone 3 240°C, zone 4 240°C, zone 5 230°C, the screw speed is 60rpm, and the composite material can be obtained by melt extrusion and granulation.

[0031] Comparative Example 1 A composite material for plastic products, comprising the following raw materials in parts by weight: High density polyethylene 70 parts; Compatibilizer 12 parts; 3 parts of medical stone fiber; 1 part of UV absorber UV-234; Antioxidant 168 1 part; 3 parts of talcum powder; 1.5 parts of paraffin; The production method of the composite material specifically comprises the following steps: Step S1, weigh and prepare the raw materials in order according to their weight and set aside; Step S2, putting the prepared raw materials into a stirring kettle, controlling the temperature to 110° C. and the rotation speed to 2500 r / min, mechanically stirring and mixing for 40 minutes, cooling and discharging the materials to form a precursor material; Step S3, feeding the precursor material into a twin-screw extruder, controlling the temperature of each zone of the extruder in sequence: zone 1 220°C, zone 2 230°C, zone 3 240°C, zone 4 240°C, zone 5 230°C, the screw speed is 50rpm, and the composite material can be obtained by melt extrusion and granulation.

[0032] Comparative Example 2 A composite material for plastic products, comprising the following raw materials in parts by weight: High density polyethylene 70 parts; Compatibilizer 12 parts; 1 part of UV absorber UV-234; Antioxidant 168 1 part; 3 parts of talcum powder; 1.5 parts of paraffin; The production method of the composite material specifically comprises the following steps: Step S1, weigh and prepare the raw materials in order according to their weight and set aside; Step S2, putting the prepared raw materials into a stirring kettle, controlling the temperature to 110° C. and the rotation speed to 2500 r / min, mechanically stirring and mixing for 40 minutes, cooling and discharging the materials to form a precursor material; Step S3, feeding the precursor material into a twin-screw extruder, controlling the temperature of each zone of the extruder in sequence: zone 1 220°C, zone 2 230°C, zone 3 240°C, zone 4 240°C, zone 5 230°C, the screw speed is 50rpm, and the composite material can be obtained by melt extrusion and granulation.

[0033] Test Case The composite materials in the examples and comparative examples were injection molded into test samples that met the specifications, and the following performance tests were performed. The test results are recorded in Table 1: Table 1 - Performance test results ; The tensile strength test reference standard is GB / T 1040.1-2018; the bending strength test reference standard is GB / T9341-2008; the impact strength test reference standard is GB / T 1843-2008.

[0034] By observing the test results in Table 1, it can be seen that the high-density polyethylene is modified by the medical stone fiber reinforcement prepared in Preparation Example 1, and a polyethylene composite material with excellent mechanical strength can be obtained. After the medical stone fiber reinforcement is replaced with conventional unmodified medical stone fiber, due to the problem of interface incompatibility, the medical stone fiber cannot efficiently exert the reinforcement effect, resulting in a poor reinforcement effect on the high-density polyethylene.

[0035] Specific examples are used herein to illustrate the principles and implementation methods of the present invention. The description of the above embodiments is only used to help understand the method of the present invention and its core ideas, including the best mode, and also enable any technician in the field to practice the present invention, including making and using any device or system, and implementing any combined method. It should be pointed out that for ordinary technicians in this technical field, without departing from the principle of the present invention, the present invention can also be improved and modified, and these improvements and modifications also fall within the scope of protection of the claims of the present invention. The scope of patent protection of the present invention is defined by the claims and may include other embodiments that can be thought of by those skilled in the art. If these other embodiments have structural elements similar to the literal expression of the claims, or if they include equivalent structural elements that are not substantially different from the literal expression of the claims, then these other embodiments should also be included in the scope of the claims.

[0036] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. Such modifications or replacements will not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for producing a composite material for plastic products, characterized in that: The composite material comprises the following raw materials in parts by weight: High density polyethylene 68-72 parts; Compatibilizer 5-15 parts; Medical stone fiber reinforcing agent 2-3.5 parts; 0.5-1.5 parts of UV absorber; Antioxidant 0.5-1.2 parts; 2-5 parts of inorganic powder additives; 1-2 parts of lubricant; The production method specifically comprises the following steps: Step S1, weigh and prepare the raw materials in order according to their weight and set aside; Step S2, putting the prepared raw materials into a stirring kettle, controlling the temperature to 100-120°C, the rotation speed to 2000-3000r / min, mechanically stirring and mixing for 30-60min, cooling and discharging the materials to form a precursor material; Step S3, feeding the precursor material into a twin-screw extruder, controlling the temperature of each zone of the extruder in sequence: zone 1 220±5°C, zone 2 230±5°C, zone 3 240±5°C, zone 4 240±5°C, zone 5 230±5°C, the screw speed is 50-60rpm, and the composite material can be obtained by melt extrusion and granulation.

2. The method for producing a composite material for plastic products according to claim 1, characterized in that: The compatibilizer is maleic anhydride grafted polypropylene or maleic anhydride grafted polyethylene.

3. The method for producing a composite material for plastic products according to claim 1, characterized in that: The preparation method of the medical stone fiber reinforcing agent comprises the following steps: Step SS1, using epoxy silane coupling agent to modify the surface of medical stone fiber to obtain fiber intermediate material; Step SS2: using toluene as a medium and under the action of a phase transfer catalyst, a macromolecular graft-modified polymer is used to carry out a grafting reaction with the fiber intermediate material to obtain a medical stone fiber reinforcing agent.

4. The method for producing a composite material for plastic products according to claim 3, characterized in that: In step SS1, the epoxy silane coupling agent is 3-glycidyloxypropyltrimethoxysilane or 3-glycidyloxypropyltriethoxysilane; the mass ratio of the medical stone fiber and 3-glycidyloxypropyltriethoxysilane is 2.6g:3.5g; in step SS2, the mass ratio of the toluene, the fiber intermediate material, the macromolecular grafted modified polymer, and the phase transfer catalyst is 20g:2.4g:6.5g:0.1g.

5. The method for producing a composite material for plastic products according to claim 3, characterized in that: In step SS2, the phase transfer catalyst is any one of tetrabutylammonium hydrogen sulfate, tetrabutylammonium bromide, tetramethylammonium bromide or tetrabutylammonium chloride.

6. The method for producing a composite material for plastic products according to claim 3, characterized in that: In step SS2, the preparation method of the macromolecular graft-modified polymer is as follows: Add diphenolic acid and toluene solvent to a polymerization kettle filled with nitrogen, start stirring after adding, and after forming a uniform solution, add sodium hydroxide aqueous solution to the polymerization kettle, start heating after adding, raise the temperature to 50-60° C., keep warm for 1-2 hours, then add a branching linker to the polymerization kettle, further raise the temperature to 70-80° C., keep warm and stir for 8-16 hours, evaporate and remove the solvent, separate the product, and obtain a macromolecular graft-modified polymer; The usage ratio of diphenolic acid, toluene solvent, sodium hydroxide aqueous solution and branching linker is 0.4 g: 2 mL: 1 mL: 0.54 g.

7. The method for producing a composite material for plastic products according to claim 6, characterized in that: The mass fraction of the sodium hydroxide aqueous solution is 20-30%.

8. The method for producing a composite material for plastic products according to claim 6, characterized in that: The branching linker is tetrabromoneopentane.

9. The method for producing a composite material for plastic products according to claim 1, characterized in that: The ultraviolet absorber is ultraviolet absorber UV-234 or ultraviolet absorber UV-120; the antioxidant is antioxidant 1076 or antioxidant 168; the inorganic powder additive is any one of talcum powder, titanium dioxide or fumed silica; the lubricant is paraffin or polyethylene wax.

10. A composite material for plastic products, characterized in that: The method is prepared by the production method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • A fiber-reinforced polyethylene plastic and its preparation method

    CN115260636B

  • Low-water-adsorbing high-impact nylon composite material and preparation method thereof

    CN109735097A

  • Functional dressing based on quaternary ammonium salt antibacterial agent and preparation method thereof

    CN118903516A